A Detailed Study on Extramedullary Hematopoiesis: Uncommon Case of Giant Adrenal Incidentaloma Mimicking Tumor Mass - ELaouni Soukaina; Znati Kaoutar (New Horizons in Medicine and Medical Research Vol. 2, 2022)
Extramedullary hematopoiesis (EMH) is a compensatory phenomenon that occurs when bone marrow function is insufficient to meet the circulatory demands. EMH is most commonly found in the reticuloendothelial system, such as the spleen, liver, and lymph nodes, as well as in para-osseous sites. EMH in the adrenal is uncommon, with fewer than ten cases reported, and presenting as a massive adrenal mass is extremely rare. We present two 38-year-old women who had -thalassemia since childhood. After excluding hormonal secretion, computed tomography (CT) revealed a giant right adrenal mass with heterogeneous density mimicking a tumour mass with moderate splenomegaly associated. An ultrasound-guided biopsy was performed, which revealed fibrocollagenous tissue with trilineage haematopoiesis in favour of adrenal EMH, ruling out malignancy. As a giant mass, the treatment consisted of excision surgery followed by iterative transfusions to prevent recurrence. In daily practise, practitioners should pay close attention to the differential diagnosis in any patient with chronic hematologic disorders suggestive of EMH, even if the location is unusual. To avoid unnecessary procedures, a confirmatory preoperative biopsy is recommended.